Pioneering death: the violence of boyhood in turn-of-the-century Oregon - Boag, Peter (Emil and Kathleen Sick series in western history and biography, 2022)
Prologue. "A scene of wholesale butchery": a document of rural ethnology -- Part I. "Aided by boys upon horseback, who carried lanterns": boyhood in rural Oregon -- "The hope and life of the nation": boys and families on the republican landscape -- "A child, sick with scarlet fever": the traumas and violences of rural childhood -- "Spare the rod and spoil the child": the bad boy problem and the Montgomery parricide -- Part II. "One by one they are dropping like the autumn leaves": agricultural decline, dying pioneers, and parricide -- "The pinching economies of life": the agrarian crisis and the murder of parents -- "His people being pioneers": parricide in an age of death and an era that celebrated killing -- Part III. "We're going to hang him right here, on this tree": killing Loyd Montgomery -- "The scaffold is all framed and ready to be put in place": executing a boy on an altar of global capitalism -- "At 14 1/2 minutes his heart ceased to beat": a boy's life from 4:30 p.m., November 19, 1895, to 7:26 a.m. January 31, 1896 -- Epilogue. "The case of Loyd Montgomery does not end with his death": burying a boy and digging up the past.